Strategies to promote better research on oral health in Africa: A Delphi consensus study - Aïda Kanoute; Daouda Faye; Denis Bourgeois (Wolters Kluwer Medknow Publications, 2014)
Background: Research on oral health contributes to improved health outcomes; it is an indispensable tool in health policy. But how to fill the gaps in research oral health and to strengthen its capacity is the question. The main objective of the present study is to identify the current status of oral health research and potential strategies, thereby strengthening the research infrastructure and capacity. Delphi consultation, in the perspective of assisting decision-makers to identify strategies to promote better research on oral health in Africa, was initiated. Design and Methods: The panels of 30 experts were asked to complete the questionnaire with 42 items into four groups by web survey. Each indicator statement was considered to be in consensus if the expert's opinion rating was of "A or B" for more than 75% in a scale of seven categories. Quantitative analysis was made from the answers of Delphi round. Results: There was a strong consensus about three items concerning the role of oral health research, the development of research policy for oral health going through an effective governance of research institutes, migration of researchers and fund raising. Conclusion: This study shows strong many dispersal opinions by experts, but highlights the need for to improve the effectiveness of oral health research capacity strengthening activities. Africa's researchers, policy makers and partners will have to give special attention to ensuring that knowledge generated from oral health research is acted on to improve health for all.